Cerebral infarct in children aged zero to fifteen years Infarto cerebral em crianças de zero a quinze anos de idade - Thelma Ribeiro Noce; Soraia Ramos Cabete Fábio; José Ibiapina Siqueira Neto; Antônio Carlos dos Santos; Carolina Araújo Rodrigues Funayama (Arquivos de Neuro-Psiquiatria)
Cerebral infarcts in children present peculiar characteristics either due to their diversity of causes or due to the unknown nature of the causes. The etiologies of cerebral infarct were reviewed in children from zero to 15 years old, attended at a tertiary hospital, in Ribeirão Preto (Brazil), from 1990 to 1997, adopting the modified Trial of ORG 10172 in Acute Stroke Treatment (TOAST) criteria of classification; 1 - Atherosclerosis in large arteries; 2 - Cardioembolic; 3 - Occlusion of small vessels; 4 - Other etiologies; 5 - Undetermined cause. Thirty-nine children were included, 18 males and 21 females, aged 2 months to 15 years, mean age 5.67. The largest group, N=22 (56.4%), included children with ''other etiologies'', 7 of them aged under two years. The most common etiology was dehydration and septic shock leading to brain hypoperfusion and watershed infarcts. Nine (23%) children had ''Undetermined etiology'', 7 (17,9%) cardioembolic subtype and none had atherosclerosis. Laboratory improvement is needed for the large number of patients without a defined cause, and the high proportion of children with dehydration in the group with a determined cause emphasizes the need for preventive health actions among infants and children. Infartos cerebrais em crianças apresentam peculiaridades, como grande variedade de causas e alta freqüência sem etiologia definida. Foram revistos os diagnósticos etiológicos em crianças de zero a 15 anos, atendidas durante o ictus e com imagens cerebrais sugestivas de infarto, entre 1990 e 1997 em hospital terciário de Ribeirão Preto (SP). Adotou-se o critério de classificação modificado do Trial of ORG 10172 in Acute Stroke Treatment (TOAST): 1 - Arterioesclerose de grandes artérias, 2 - Cardioembólico, 3 - Oclusão de pequenos vasos, 4 - Outras etiologias, 5 - Não determinada. Trinta e nove crianças foram incluídas, 18 do sexo masculino e 21 do feminino, com idade variando entre 2 meses e 15 anos e média de 5,67. O maior grupo, com 22 crianças (56,4%), foi o de ''Outras etiologias'', 7 das quais com idades entre 2 meses e um ano. A etiologia mais freqüente foi desidratação e choque séptico, levando a hipoperfusão cerebral e infarto em zonas limítrofes. Nove (23%) com etiologia não determinada constituiram o segundo grupo, 7 (17,9%) apresentaram causas cardioembólicas e nenhum caso foi registrado com arteriosclerose. Ressalta-se a necessidade de investimento laboratorial, considerando-se a alta freqüência de casos sem diagnóstico. O alto número de crianças com infarto decorrente de desidratação requer atenção para ações preventivas em saúde infantil.